2023
DOI: 10.3390/ijms24076496
|View full text |Cite
|
Sign up to set email alerts
|

Lupin, a Unique Legume That Is Nodulated by Multiple Microsymbionts: The Role of Horizontal Gene Transfer

Abstract: Lupin is a high-protein legume crop that grows in a wide range of edaphoclimatic conditions where other crops are not viable. Its unique seed nutrient profile can promote health benefits, and it has been proposed as a phytoremediation plant. Most rhizobia nodulating Lupinus species belong to the genus Bradyrhizobium, comprising strains that are phylogenetically related to B. cytisi, B. hipponenese, B. rifense, B. iriomotense/B. stylosanthis, B. diazoefficiens, B. japonicum, B. canariense/B. lupini, and B. reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Recently, it has been shown that varying degrees of metal stress in the local population may increase the frequency of HGT events [23], providing a source of adaptive evolution in bacteria [22] in contaminated environments. Moreover, HGT is also crucial in rhizobia to determine their host range [77]. And while we typically expect selection to act on standing genetic variation in a species [78], the mechanism of HGT can cross species boundaries, accelerating adaptation, even if the donor genetic locus is at low frequency in the population [79] or in the microbiome of the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that varying degrees of metal stress in the local population may increase the frequency of HGT events [23], providing a source of adaptive evolution in bacteria [22] in contaminated environments. Moreover, HGT is also crucial in rhizobia to determine their host range [77]. And while we typically expect selection to act on standing genetic variation in a species [78], the mechanism of HGT can cross species boundaries, accelerating adaptation, even if the donor genetic locus is at low frequency in the population [79] or in the microbiome of the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that varying degrees of metal stress in the local population may increase the frequency of HGT events (Chen et al, 2023), providing a source of adaptive evolution in bacteria (Arnold et al, 2022) in contaminated environments. Moreover, HGT is also crucial in rhizobia to determine their host range (Msaddak et al, 2023). And while we typically expect selection to act on standing genetic variation in a species (Barrett and Schluter, 2008), the mechanism of HGT can cross species boundaries, accelerating adaptation, even if the donor genetic locus is at low frequency in the population (Woods et al, 2020) or in the microbiome of the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these described mechanisms render white lupin a suitably adapted plant for acidic soil conditions impacted by aluminum toxicity [ 8 ]. Its capacity to thrive in environments with low nutrient content, acidity, or moderate pollution levels, as well as in both dry and cold climates, allows this legume to grow in a wide range of edaphoclimatic conditions [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%